Exercise for adolescents with depression: valued aspects and perceived change. Issue 1 (19th August 2015) - Carter, T.; Morres, I.; Repper, J.; Callaghan, P.
Abstract : Accessible summary: What is known on the subject?: There is evidence suggesting that exercise may be effective at reducing depression in adults and young people; however, there is no research exploring how adolescents with depression experience exercise interventions. What the paper adds to existing knowledge?: This study presents the experiences of 26 adolescents with depression who undertook an innovative preferred intensity exercise programme. Important insights relating to benefits and aspects of the preferred intensity exercise emerged. Specifically, the adolescents experienced feelings of improved mood, achievement and enjoyment, alongside numerous benefits. What are the implications for practice?: Given that mental health nurses are in key positions to promote physical exercise for this target group, this paper suggests that when promoting exercise they should consider that preferred intensity exercise may provide a series of valuable mental health benefits without the need for fixed intensity training. Abstract: Introduction: Despite systematic reviews demonstrating an association between exercise participation and reduced depressive symptoms in young people, there is no qualitative research exploring the experience of depressed adolescents who have engaged in an exercise intervention. Aims: To explore the experience of depressed adolescents who had recently engaged in a preferred intensity exercise intervention. Method: The participants ( n = 26) were recruited through health and social care services, were all in treatment for depression, and were purposefully sampled for interview following engagement in a preferred intensity exercise intervention, which was being evaluated via a pragmatic randomized controlled trial. A thematic approach was undertaken to analyse and organize the data. Results: Numerous beneficial changes were reported by participants alongside specific aspects of the intervention that were valued. Discussion and implications: The findings suggest that preferred intensity exercise can lead to feelings of improved mood, enjoyment and achievement, alongside benefits that transcend depressive symptom reduction. Considering mental health nurses are in key positions to promote exercise in this population, the current findings provide vital information for this purpose.